Synthesis of Dy2O3-ZrO2 nano powders by cocurrent coprecipitation - CHENG Huicong; WANG Yalei; LI Axin; LIU Huaifei; WU Nannan; LIU Rong (Cailiao gongcheng, 2022)
Nano-sized Dy2O3 doped ZrO2 powders (DySZ) were synthesized by cocurrent co-precipitation method. The effects of Dy2O3 content, cation concentration, pH value and calcination temperature on the phase composition, crystal structure, grain size and micromorphology of DySZ powders were investigated. Results show that under different synthesis conditions, the spherical DySZ powders have nano scale characteristics with a size range of 10-30 nm, Dy2O3-doping can promote the DySZ stabilized as tetragonal structure. The doping amount of stabilizer has a significant effect on the phase composition of DySZ powder. Single tetragonal DySZ can be obtained with 10%(mass fraction) Dy2O3-doping. No significant effect can be found between the tetragonality, microstructure of DySZ powders and the stabilizer content, cation concentration, pH value as well as calcination temperature. The average grain size exhibits a slight decrease with the increase of stabilizer content, cation concentration and pH value. Meanwhile, the elevated calcination temperature can promote the crystal growth of DySZ.